Effect of cell culture system on the production of human viral antigens - Mendonça,Ronaldo Zucatelli (2004)
A comparative study was performed in the production of different viral antigens by using microcarrier systems and traditional systems. Vero, BHK and MA 104 cells were cultivated in microcarriers (2mg/ml) using a bioreactor with a working capacity of 3.7 liters, in parallel with conventional Roux bottles. After four days (BHK cells), and seven days of culture (Vero and MA-104 cells), the cells were infected with 0.1 MOI (multiplicity of infection) of rabies virus, measles virus, poliovirus and rotavirus. The yields of the cells and virus in microcarriers and in the conventional system were determined. It was observed that in the microcarrier system, an average increase of twenty-fold more cells/ml was obtained in relation to the conventional monolayer culture, using Roux bottle. On the other hand, cells grown in Roux bottles presented 1.3 to 6.7 more viruses/ml culture than those in the microcarrier systems. However, the overall data showed that yieldings, in terms of viruses per batch, were statistically similar for both systems (p > 0.05). The amount of viral antigen production seems to depend not only on cell concentration, but also on other culture factors such as the characteristic of the cell-growth surface. Thus, the present findings provide a baseline for further improvements and strategies to be established for a scaling-up virus production since depending on the type of virus the optimal conditions found for a small-scale virus production seem unsuitable for large-scale production, requiring new standardization and evaluation.